INFECTION PROCESS OF ENTOMOPATHOGENIC FUNGI Metarhizium anisopliae IN THE Tetranychus kanzawai (KISHIDA) (TETRANYCHIDAE: ACARINA) - Sanjaya, yayan; Ocampo, Virginia R.; Caoili, Barbara L. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
The importance of fungal attack to acarina has been observed but not yet on Tetranychus kanzawai. When infected mite, either within in a same species or even in a different species of entomopathigenic probably have similar signs and simptoms to mites. Characteristic of entomopathogenic fungus to Tetranychus kanza-wai was investigated. Three selected isolates of Metarhizium anisopliae, from Philippines and Indonesia were evaluated. The following aspects were investigated: (1) Bioassay tes of virulence, (2) Koch Postulate and (3) Infection process on each fungus against mite. Virulence of Metarhizium anisopliae was 1.4 X 103, 7.2 X 102 , 5 X 102 PIB per ml on Ma4, Ma5 and Ma6, respectively. On Koch Postulates, Reinoculation and reisolation of all seven isolates from infected T. kanzawai showed definite signs of infection. This demonstrated its entomopathogenic capacity. In this experiment, adult mites were sprayed with 108 per ml concentrations of conidia observed under light microscope and Scanning Electron Microscopy (SEM). The result found T. kanzawai was very susceptible to three isolates M. anisopliae. In the end of the trials, fungal growth was detectable as early as 2 until 4 days of observation. Infection process with microphoto-graph and Scanning Electro Microscopy showed attachment, germination and penetration, extrusion and conidiogenesis fungal form. Keywords: Infection, Tetranychus kanzawai, Metarhizium anisopliae, Light micros-copy, Scanning Electro Microscopy (SEM)